Significativos estudantis e institucionais atribuídos ao uso de álcool e outras drogas em uma Universidade federal - Lima, Karla Helene Marques [UNIFESP] (2015)
Distinct moral and political positions mark the social significance of drugs in contemporary. However, there is a concensus that such phenomenon is complex and several ideological questions present themselves revealing multifaceted social aspects that are not neutral. This research aims to understand the meanings attributed to the use of alcohol and other drugs by the students of the Federal University of São Paulo- campus Baixada Santista (UNIFESP), as well as to analyse the institutional meanings tied to the domestic policies about drugs at the university. The hypothesis is that the institutional and experiencial diversity in the understanding of the consunption of alcohol and other drugs are subject to the official discourse. This setting is historically reiterative of the hegemonic positions and could compromise the most assertive and effective policies in relation to drug education. The methodology is quantitative and the production of data was performed by semi-structured interviews, research diaries, and documentary survey on alcohol and other drugs (management reports, newspapers, websites, articles and other printed materials from the university). For the data organization a table, which helped define the canalysing categories, was built.The first category was called Drugs at the University: silences and dialogues; the second Youth and the University and the third Harm Reduction: the university dilemma. Data analysis was conducted by the means of Content Analysis and Triangulation. The conclusion, through the categories analysed, shows that in spite of the dialogue fostered by the Pro Rectory of Student Affairs at UNIFESP, there are still gaps in the discussion about the use of alcohol and other drugs on the Baixada Santista campus, urging the university to fulfill its pedagogical role and to incorporate this theme in the formative spaces at UNIFESP. Concerning the meanings presented by the students, on the reasons for consumming alcohol and other drugs, among the many scopes there are: its use as a refuge, to sharpen criativity, to be able to study. Nevertheless, the most evident meaning was the relation between the use of psychotropic substances and the processes of socialization and leisure. Regarding the places where the use of drugs is potentialized some territories such as parties- specially the ones organized by the Athletic Club, luaus and matches stand out. This study is expected to contribute to the construction of health care strategies and harm reduction allied to the enhancement of the students' authonomy towards the use of alcohol and other drugs.